The DIAMORFOSIS (DIAgnosis and Management Of lung canceR and FibrOSIS) survey: international survey and call for consensus - Argyris Tzouvelekis (ERJ Open Research, 2021)
Background Currently there is major lack of agreement on the diagnostic and therapeutic management of patients with idiopathic pulmonary fibrosis (IPF) and lung cancer. Our aim was to identify variations in diagnostic and management strategies across different institutions and provide rationale for a consensus statement on this issue. Methods This was a joint-survey by European Respiratory Society (ERS) Assemblies 8, 11 and 12. The survey consisted of 25 questions. Results Four hundred and ninety-four (n=494) physicians from 68 different countries and five continents responded to the survey. Ninety-four per cent of participants were pulmonologists, 1.8% thoracic surgeons and 1.9% oncologists; 97.7% were involved in multidisciplinary team approaches on diagnosis and management. Regular low-dose high-resolution computed tomography (HRCT) scan was used by 49.5% of the respondents to screen for lung cancer in IPF. Positron emission tomography (PET) scan and endobronchial ultrasound (EBUS) is performed by 60% and 88% to diagnose nodular lesions with mediastinal lymphadenopathy in patients with advanced and mild IPF, respectively. Eighty-three per cent of respondents continue anti-fibrotics following lung cancer diagnosis; safety precautions during surgical interventions including low tidal volume are applied by 67%. Stereotactic radiotherapy is used to treat patients with advanced IPF (diffusing capacity of the lung for carbon monoxide (DLCO) <35%) and otherwise operable nonsmall cell lung cancer (NSCLC) by 54% of respondents and doublet platinum regimens and immunotherapy for metastatic disease by 25% and 31.9%, respectively. Almost all participants (93%) replied that a consensus statement for the management of these patients is highly warranted. Conclusion The diagnosis and management of IPF-lung cancer (LC) is heterogeneous with most respondents calling for a consensus statement.